Broadband Infrastructure and Economic Growth: A Panel Data Analysis of OECD Countries - Syed Muhammad Atif; James Endres; James Macdonald (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
Broadband infrastructure facilitates the generation and distribution of decentralised information and ideas in a knowledge economy comprising of markets that rely on information as an input. This paper analyses the effect of broadband penetration on output per capita by estimating a static fixed effects model and a basic linear dynamic model using an annual panel of 31 OECD countries over a period from 1998 to 2010. The results suggest that broadband penetration has had a positive impact on economic growth, and a 10 percent increase in the growth of broadband penetration will raise economic growth per employee by approximately 0.035 percentage points. The conclusion adds further weight to calls for Governments to adopt policies that accelerate broadband penetration and promote investment in broadband infrastructure.
Keywords: O11; O33; 330; Endogenous Growth; Broadband; OECD; Endogeneous technical change; OECD countries